Dynamic Effects in yhe Rail Vehicle-Track System for Elastic-Plastic Foundation - Grzyb, A. (Engineering Transactions, 1995)
The paper is devoted to elaboration of a simulation method for an infinite straight Timoshenko beam on the elastic-plastic foundation with nonsymmetric characteristic under moving load. The inertialess distributed load moves along the beam with a constant velocity. This beam can be considered as a railway track and the loads as a train moving on the track. The stationary solution for the nonlinear equation was obtained by means of the approximation method applying the analytical solution for the case of the linear approach. Same results of the numerical calculations of dimensionless displacements are shown in the Figs. 3-7. The plastic deformation of the beam connected with the assumed elastic-plastic characteristic of foundation have been determined. The numerical program allows to sum up the plastic displacements computed in successive passing of the load. These dimensionless plastic deformations are shown in the Tables 2-5. The possibility of track destruction as a result of incorrect operation has also been considered.